2021
DOI: 10.7759/cureus.13373
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Role of Calretinin in Suspicious Cases of Hirschsprung’s Disease

Abstract: Background Hirschsprung's disease (HD) is a developmental disorder of the intrinsic component of the enteric nervous system. It is characterized by the absence of ganglion cells in the myenteric and submucosal plexus. Histopathological diagnosis becomes difficult many times due to submucosal ganglionic cells are not easily identifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…23,24 With a male-to-female ratio of 3.6:1, which is analogous to the universal ratio of 2.9: 1 to 4.5: 1, the current study demonstrated that males were more afflicted than females, 25 75% of our HD-positive patients were suffering from chronic constipation which is compatible with other published studies. 23,26 The second most frequent symptom was delayed meconium passage, while 10% of children reported intestinal obstruction, and our clinical assessment was consistent with the clinical findings in the literature. 24 Rectal biopsy continues to be the gold standard for definitively diagnosing HD.…”
Section: Discussionsupporting
confidence: 88%
“…23,24 With a male-to-female ratio of 3.6:1, which is analogous to the universal ratio of 2.9: 1 to 4.5: 1, the current study demonstrated that males were more afflicted than females, 25 75% of our HD-positive patients were suffering from chronic constipation which is compatible with other published studies. 23,26 The second most frequent symptom was delayed meconium passage, while 10% of children reported intestinal obstruction, and our clinical assessment was consistent with the clinical findings in the literature. 24 Rectal biopsy continues to be the gold standard for definitively diagnosing HD.…”
Section: Discussionsupporting
confidence: 88%
“…Jorge et al reported an average of 2.7 months (approximately 80 days) in their sample with only calretinin IHC diagnostics [1]. Singh et al were able to diagnose 73% of all HD patients within the first 28 days of life using calretinin IHC [17]. Calretinin enables the diagnosis of HD to be made at any time.…”
Section: Discussionmentioning
confidence: 99%
“…They reported sensitivity of calretinin as 100%, specificity as 68.75%, and positive and negative predictive values as 85.33% and 100%, respectively. 9 Under light microscopy the ganglion cells are identified by their classic cytological features. They have sufficient cytoplasm, nucleus is to one side and it is round and have a prominent nucleolus.…”
Section: Discussionmentioning
confidence: 99%